Lietuvos istorija dokumentiniame kine ir televizijoje. Diskurso konstravimo ypatybės - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2004)
The aim of the article was to take a look at the peculiarities of construction of historical discourse in documentary cinema and television from the perspective of the contemporary history science. The raised goal was specified by the following tasks:  1. To motivate the beginning and relevance of the selected research in the introductory part;  2. To describe the essence of audio-visual history following the works of Western (mainly German) authors;  3. To discuss the particularity of documentary films and broadcasts dealing with historical topics which have been created during Lithuania's independence, having employed a certain classification.  The article considers presentations with historical content and expressed in audio-visual language as audio-visual history. They are determined by internal (particularity of audio-visual language as the means of creation and perception of the way of expression, genre requirements) and external (concepts of purpose of institutions that create audio-visual history which range between conveyance, entertainment, and society education; their wish to please the audience and survive in competition) factors.  A great number of documentary films and thematic broadcasts dealing with audio-visual history have been created during Lithuania's independence. Classification has been employed in order to describe their construction particularities. The criterion of such classification is an implicit concept of history's purpose created by authors; selection of "construction material," organization, and eventually the nature of predominant information depend on this concept. Based on it, three groups of audio-visual history have been distinguished: factographic (with problematic history as its "branch"), ethical, and aesthetical.  The intention of the authors of factographic history is history as the means for cognition of the past. This concept determines selection of "reliable" sources of knowledge (scientific works) and commentators (professionals), demonstration of abundant adjusting and/or iconographic material. Problematic history should be perceived as a separate "branch" of factographic history. It is characterized by a focus on the modern actualities of social historic consciousness and emphasis on the problems of the cognition of the past and the reconstructional nature of history.  The second group of historical discourses has been identified as an ethical group. It focuses on the axiological information on the past. The main source of historical information in the broadcasts and films of such nature is individual or collective memory recorded by audiovisual technical means. The discourses emphasizing an ethical part of the past often do not provide historical context and lack criticism with regard to memorized contents.  The third group of history discourses has been identified as aesthetic. The products of this group are distinguished from the other broadcasts and films by a particular emphasis placed by the creators on the forms of historical art and their specific presentation, which highlights their aesthetic information rather than documentary value.